Fantasma, mito y dibujo en la enseñanza de Lacan (2011)
ABSTRACT: This article provides detailed explanations to the psychoanalytical debate about the symbolic value of the drawing in the clinical institution from Lacan lessons. First, some of the main relations where Lacan establishes associations between the human myths and concepts of "neurotic individual myth" and "phantom" are shown. Next the author's postures about the functions meaning, word, and symbolic have in phantom construction are described, showing the images also can symbolize for the author a meaningful function that favor traffic between imaginary and symbolic. After the study of these Lacan lessons the idea that images are only part of the imaginary record is questioned, based on this idea from some postures there is a tendency to restrict the clinical work to word usage, excluding directly the use of other symbolic means, as the draw, controversial point of view in this essay. Finally, the main Lacan’s ideas about the meaning and symbolic functions of the image, more specifically the drawing in phantom construc-tion are presented.